Predictive Value of Prospective Memory for Remission in First‐Episode Schizophrenia. Issue 2 (20th June 2013) - Zhou, Fu‐Chun; Xiang, Yu‐Tao; Wang, Chuan‐Yue; Dickerson, Faith; Kreyenbuhl, Julie; Ungvari, Gabor S.; Au, Raymond W. C.; Zhou, Jing‐Jing; Zhou, Yan; Shum, David; Man, David; Lai, Kelly Y. C.; et al.
<x xml:space="preserve">Abstract</x> Purpose The study examined the rate of remission in individuals experiencing a first episode of schizophrenia (FES) in China and explored predictors of remission in the acute phase of the illness. Design and Methods Fifty‐five FES patients were randomly treated with risperidone, olanzapine, or aripiprazole at therapeutic doses for 8 weeks, and their clinical profiles and cognition were assessed using standardized assessment instruments at entry and the end of the study. Findings Of the 55 patients, 30 (54.5%) remitted by the end of the 8‐week study. In univariate analyses, shorter duration of untreated psychosis, higher scores on both the time‐based prospective memory (TBPM) and event‐based prospective memory tasks and the Hopkins Verbal Learning Test‐revised, and less severe negative symptoms were significantly associated with remission. In stepwise multiple logistic regression analyses, only higher scores on the TBPM significantly predicted remission. Individuals having higher scores reflecting better TBPM at baseline were more likely to achieve remission after 8 weeks of optimized antipsychotic treatment. Practice Implications TPBM may be useful in helping clinicians identify those FES patients most likely to achieve a favorable treatment response.